The impact of the Pentagram's strategy on academic achievement of Jordanian basic school students in Islamic education and their attitudes toward it - Talhouni, Mansour Hamed; Al-Mawajdeh, Baker Sameeh; Al-Khattab, Ahmad Adnan (Frontiers in Education, 2025)
This study aimed to explore the impact of Pentagram's strategy on the academic achievement of Jordanian tenth-graders in Islamic education and their attitudes toward it. The study sample consisted of (77) tenth-grade students from Tareq Bin Ziyad Basic School in Marka District, Amman, and was divided into experimental (38 students) and control (39 students) groups. Two tools were used: an achievement test and a scale measuring attitudes toward Islamic education, after being verified for validity and reliability. The results indicated a significant impact of the Pentagram strategy on students' achievement and attitudes in Islamic education when comparing the results of both groups. Therefore, the study recommended encouraging teachers to construct Islamic education courses at other levels and classes in accordance with the Pentagram strategy has proved effective in the present study in achieving and developing attitudes among students toward Islamic education. Another recommendation was that training programs for teachers to practically implement the Pentagram strategy so they implement them in classrooms.